2022
DOI: 10.3389/fgene.2022.775123
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Bilateral Absence of the Vas Deferens

Abstract: Congenital bilateral absence of the vas deferens (CBAVD) is clinically characterized by the absence of the bilateral vas deferens; the main clinical manifestation is infertility, accounting for 1–2% of male infertility cases. CBAVD may be accompanied by congenital abnormalities in the urogenital system and cystic fibrosis (CF)-related clinical manifestations. CBAVD can develop as a mild manifestation of CF or can be isolated. The main pathogenic mechanism of CBAVD is gene mutation, and CBAVD and CF have a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Males often face an obstruction of the vas deferens, which carries sperm from the testes to the penis; the vas deferens may even be absent (Cai & Li, 2022). The obstruction is often encountered in CF (Cui et al, 2020).…”
Section: Reproductive Systemmentioning
confidence: 99%
“…Males often face an obstruction of the vas deferens, which carries sperm from the testes to the penis; the vas deferens may even be absent (Cai & Li, 2022). The obstruction is often encountered in CF (Cui et al, 2020).…”
Section: Reproductive Systemmentioning
confidence: 99%
“…In the absence of a vas deferens, sperm cannot pass through the epididymis and results in a low volume, acidic, azoospermia. This is a significant risk factor for infertility as 95% of men with cystic fibrosis are found to have this manifestation bilaterally, making natural conception impossible [27]. Counseling should focus on the ability to surgically obtain sperm for use with IVF.…”
Section: Key Pointsmentioning
confidence: 99%
“…It has been reported that genetic variants in CBAVD patients can affect spermatogenic function and sperm quality, thereby interfering with the ART outcome. In addition, there is a risk of passing on pathogenic genetic variants to offspring 13 . A novel comparison of CFTR variants and fertility outcomes of patients with either CF or CBAVD alone found that CF men were more likely to exhibit lower sperm quality, greater difficulty with sperm retrieval, and worse ICSI outcomes compared with CBAVD-only patients 14 .…”
Section: Introductionmentioning
confidence: 99%